Impact of the Quality of Financial and Banking Applications Used on Smartphone on the Customer Satisfaction of Jordanian Islamic Bank - AL-Habashneh, Amjad Ghazi; Mohammad, Suleiman Ibrahim Shelash; Vasudevan, Asokan; Al-Adwan, Ahmad Samed; Mohammad, Anber Abraheem Shlash; Jiang, Lan Qing (International Review of Management and Marketing, 2024)
This study aimed to identify the impact of the quality of financial and banking applications through the dimensions of (information security, trust, privacy) used on smartphones on the satisfaction of Jordanian Islamic bank customers. The researcher employed a descriptive-analytical approach in constructing the study. The study population consisted of all customers of Jordanian Islamic banks. The researcher developed a research tool (a questionnaire) to align with the study’s dimensions. A random sample of Islamic bank customers was selected, and the research tool was distributed to them electronically. The researcher was able to obtain responses from 249 participants. One of the key findings of the study was that there is a high level of usage of financial and banking applications on smartphones in Islamic banks. Among the dimensions, “privacy” ranked the highest in importance based on the participants’ responses. The results also revealed a significant impact of the quality of financial and banking applications used on smartphones, through the dimensions of (information security, trust, and privacy), at a significance level of (α ≤ 0.05) on the satisfaction of Jordanian Islamic bank customers. Among the key recommendations was the need for greater focus on quality factors related to financial and banking applications by emphasizing the dimensions of information security, trust, privacy, and data protection due to their significant role and impact on customers using these applications. Additionally, there is a potential for further research and studies on the factors affecting the quality of financial and banking applications on smartphones for electronic banking services offered to customers.